Leaf through this book! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Edible Leaves of the Tropics. F Martin, R Ruberté, and L Meitzner. 1998. 194 pp. ISBN 0 9653360 1 8 $14.95 (e13.85) + $4 (e3.70 for postage) Educational Concerns for Hunger Organisation (ECHO). 17430 Durrance Road, North Fort Meyers, FL 33917 2239,